Quantitative MRI relaxometry in brain tumor needle biopsies: Multimodal comparison with tissue fluorescence, radiology, and neuropathology - Elisabeth Klint; Anders Tisell; Ida Blystad; Martin Hallbeck; Teresa Nordin; Jan Hillman; Johan Richter; Karin Wårdell (PLoS ONE, 2025)
Background Quantitative MRI (qMRI) relaxometry holds potential for brain tumor identification beyond contrast enhancement on conventional images. However, clinical implementation is limited by long acquisition times, changing conditions between imaging and surgery, and lack of correlation with standard techniques. Purpose To extend a methodology for multimodal data analysis to relaxometry data. To integrate relaxometry into the burr hole needle biopsy procedure with optical guidance, setup a workflow for multimodal data processing and analysis, and apply the methodology in a clinical setting. Methods Multi-dimensional multi-echo relaxometry data (2x6 min) was acquired in addition to the clinical imaging protocol. Relaxation rate and proton density maps, as well as their differences were calculated before (R1, R2) and after gadolinium contrast-agent administration (R1Gd, R2Gd). Radiological volumes of interest (VOIs: tumor, edema, white matter, and biopsy) were defined on clinical images. Rate distribution changes were analyzed on three levels: the biopsied volume, along the needle trajectory (4x4x4 mm3 volumes), and VOIs. Increased R1Gd and R2Gd were compared to indications from 5-aminolevulinic acid-induced fluorescence and detailed neuropathological evaluation. Results Neuropathological analysis confirmed seven glioblastoma, one lymphoma, and one non-tumorous diagnosis. Increased R1Gd was found in all biopsied volumes, although tumorous volumes presented larger R1Gd increase (3–9 times) compared to volumes dominated by necrotic or non-tumorous tissue. Along the trajectory, increased R1Gd and R2Gd were not tumor-specific, however, the greatest R1Gd shifts were found in or adjacent to radiologically defined tumorous tissue. Increased relaxation rates corresponded to 82% and 45% (R1Gd: φ = 0.35, R2Gd: φ = 0.27) of fluorescence peaks. In the radiological VOIs, increased R1Gd and R2Gd were found in tumorous tissue, a slight right shift in edematous tissue, and negligible changes in white matter. Conclusion Combined analysis suggests increased R1Gd together with fluorescence peaks as a marker for tumor tissue. The presented multimodal approach provides a workflow toward clinical translation of relaxometry.